A quality improvement initiative to improve transport team mobilization for emergent neonatal transfers - Sohane, Arpit; Kaur, Arshdeep; Suryawanshi, Pradeep; Verma, Arjun; Patnaik, Suprabha (Frontiers in Pediatrics, 2025)
IntroductionA considerable number of neonatal deaths can be attributed to delays in accessing appropriate medical care or the absence of reliable systems for transferring newborns to advanced care centers. Infants requiring urgent transfer to specialized neonatal units are particularly vulnerable, often due to the limited capabilities of peripheral birthing facilities, the absence of structured neonatal transport networks, and the reliance on unsafe or uncoordinated transfer methods. Approximately 25% of neonatal transfers are time-sensitive and require specialized neonatal teams to respond promptly. Any delay in the mobilization of the retrieval team can adversely affect the delivery of this essential time-sensitive care.MethodsThis single-center quality improvement (QI) study was conducted at a tertiary care center with a Level 3B NICU. We aimed to reduce our MT to ≤10 min in >70% of emergent neonatal transfers within 3 months. Multiple change ideas and Plan-Do-Study-Act (PDSA) cycles (designation of transport nurse, education regarding timely mobilization, keeping prechecked retrieval kit, keeping all equipment together) were carried out.ResultsMT was reduced to ≤10 min in 70.6% of transfers, and MT was under 15 min in 80.6% of emergent neonatal transfers, achieving the benchmark of 15 min given for “launch time” by the Australian New Zealand Neonatal Retrieval Network (ANZNRN) 2022 data dictionary.ConclusionEffectively formulated and executed QI strategies can accelerate the benchmark time-related quality indicators for urgent neonatal transport teams during critical neonatal transfers. Our study encourages other healthcare setups to improve MT through simple yet effective measures.